Design of a timed and controlled release osmotic pump system of atenolol. (June 2015) - Xue, Yingna; Yu, Shihui; Wang, Hanbing; Liang, Jingge; Peng, Junjie; Li, Jiang; Yang, Xinggang; Pan, Weisan
Abstract The objective of the article was to design a novel timed and controlled release osmotic pump (TCOP) containing atenolol as an active pharmaceutical ingredient and compare with a bilayer-core osmotic pump (BCOP) of atenolol. Different from BCOP, a modulating barrier was added to delay the drug release and obtain desired lag time (Tlag). The influences of the amount of pore-forming agent and modulating barrier, coating weight gain on the lag time (Tlag) and drug release rate (Rt) of TCOP were investigated. The central composite design-response surface methodology (RSM) was applied to optimize the formulation. Rhodamine B was added to modulating barrier to determine the release process of modulating barrier. A method used to correct the release profiles with a certain lag time by ΔTlag and interpolating was applied to compare TCOP with BCOP. Tlag was directly proportional to the amount of modulating barrier and coating weight gain, but inversely related to the amount of pore forming agent, which were contrary to the effects on Rt. The optimal formulation including 60 mg PEO WSR N80, 3 g PEG 4000 and 6% coating weight gain could obtain a 3.59-h Tlag. According to the release of Rhodamine B, the modulating barrier was completely pushed out at ∼5.0 h, longer than 3.59 h, therefore, atenolol along with remaining modulating barrier was released together between 3.59 and 5.0 h. By comparing with BCOP, the release profiles subtracting the part of lag time had no significant difference, yet Rt of TCOP presented a slight decrease.